Experimental determination of effective X-ray attenuation coefficients of 3D-printed materials under clinical mammography spectra - Belarra, Adrián; Hernández-Girón, Irene; Garayoa, Julia; Martínez, Luis Carlos; Valverde, Julio; Rot, María José; Ferrando, Alejandro; Martín, Antonio; Chevalier, Margarita (Frontiers in Bioengineering and Biotechnology, 2026)
Background3D printing enables the fabrication of customized breast phantoms for image quality assessment in digital mammography (DM) and digital breast tomosynthesis (DBT). A major challenge is the absence of standardized, accessible methods to characterize the attenuation properties of 3D-printed materials under clinical DM/DBT spectra.MethodsAn experimental framework was implemented to determine the effective X-ray attenuation coefficient (μeff) of six 3D-printed polymers (PLA, PET, resin, ABS, ABS+, HIPS) and reference breast tissue-equivalent materials (CIRS plates simulating different breast glandular/adipose ratios (BR) and PMMA) using two commercial DM/DBT systems, with and without anti-scatter grid. Step-wedges (0.5–5.5 cm) were imaged across multiple kVp and filter settings. The μeff were obtained from measurements on images and fitted to an empirical model yielding μ0 (attenuation at thickness tending to zero) and k (decay rate) to characterize beam hardening and scatter influences. 3D-reference material equivalences were evaluated based on μeff and μ0.ResultsBeam hardening and scatter reduced μeff with thickness, by 6%–14% with grid and 12%–28% without grid, with scatter contributing 47%–76% of the reduction in no-grid acquisitions. No significant differences were observed between the two mammography systems. Based on μeff values, attenuation equivalences (within ±6%) were identified between 3D-printed and reference breast tissue-equivalent materials: PLA with BR 100/0; PET and resin with BR 70/30 and PMMA; ABS+ with BR 30/70 and BR 50/50. ABS and HIPS showed larger mismatches. The empirical model achieved excellent fits (R2 > 0.99), with μ0 values preserving attenuation ranking and enabling derivation of equivalent glandular proportions.ConclusionThis framework demonstrates that routine clinical mammography systems can be used directly, without specialized instrumentation, to characterize 3D-printed materials as tissue surrogates. Several low-cost, widely available polymers were shown to reproduce breast tissue attenuation, supporting the local fabrication of anthropomorphic breast phantoms for realistic and clinically relevant image quality evaluation.